The role of Open Budget in achieving of the transparency and responsibility and Reflect it on the administrative and financial corruption - فليح, حكيم حمود (Journal of Economics and Administrative Sciences, 2016)
AbstractThe open budget means everyone in the society can get information about the government budget in order to watch the governmental works. The aim of the research is to study the concepts of open budget, its advantage, limitations, role of supporting the transparency and questioning the administrative and financial corruption. Thus reflects positively on the national economy by providing governmental information to all users whether they are individuals or belong to the political class, or any other governmental or nongovernmental organizations which are interested in these information.In order to achieve the objectives of the research aims, we make questionnaire to see academic accounting and auditing professors and specialists' opinions. The questionnaire is Divided into three axes including twenty-one questions.We Conclusions the following:  the government should use the open budget method to enhance the transparency and questionings to reduce the administrative and financial corruption by allowing different users watching the accounting information and the ways of spending the public funds.We have reached to a set of recommendations; the government should use the Open Budget method because it contributes to the reduction of administrative and financial corruption by allowing all users of accounting information watching the spent public funds which leads to enhance the transparency and accountability contributions in order to reduce the administrative and financial corruption.